Replication package for paper Labor Market Competition and Xenophobia: A Regional Analysis of Labor Market Competition in Europe 2010-2020. - Kawalerowicz, Juta (Stockholm University, 2025)
Replication package for Labor Market Competition and Xenophobia: A Regional Analysis of Labor Market Competition in Europe 2010-2020.

This analysis uses third party datasets: EU-LFS and ESS data.

Analysis was carried out in Stata (.do files include analysis and .dta files are datasets)

*To apply for access to EU-LFS visit https://ec.europa.eu/eurostat/web/microdata/european-union-labour-force-survey

*To download ESS data visit https://ess.sikt.no/en/data-builder/
Keywords: Sociology not elsewhere classified; Sociology; Sociologi